Strategi Pengelolaan Limbah Medis Rumah Tangga Selama Pandemi Covid-19 - Resa Mailina; Zakianis Zakianis (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; COVID-19 has an impact on various fields including the environment and waste management. Prevention of COVID-19 by using masks has another impact, namely the emergence of piles of household medical waste. Aim; to determine the management of household medical waste both in Indonesia and abroad. Method; a literature review of articles that discuss waste management in Indonesia and abroad. Result; management of medical waste at the household level in Indonesia has been regulated in Circular Letter Number SE.3/MENLHK/PSLB.3/3.2021 concerning Management of Hazardous Waste and Waste from Handling Coronavirus Disease-19. However, the implementation has not been maximized due to the lack of waste management facilities at the household level. Overseas medical waste management in some countries uses household-level segregation where medical waste is separated and processed using incinerators. Conclusion; the problems that arise are basically the same both in Indonesia and abroad are related to public awareness and unequal facilities. Recommendation; Household waste management facilities are expected to be improved along with the provision of education and knowledge to increase public awareness.